Human Cytochrome P450 3A4 as a Biocatalyst: Effects of the Engineered Linker in Modulation of Coupling Efficiency in 3A4-BMR Chimeras - Degregorio, Danilo; D'Avino, Serena; Castrignanò, Silvia; Di Nardo, Giovanna; Sadeghi, Sheila J.; Catucci, Gianluca; Gilardi, Gianfranco (Frontiers in Pharmacology, 2017)
Human liver cytochrome P450 3A4 is the main enzyme involved in drug metabolism. This makes it an attractive target for biocatalytic applications, such as the synthesis of pharmaceuticals and drug metabolites. However, its poor solubility, stability and low coupling have limited its application in the biotechnological context. We previously demonstrated that the solubility of P450 3A4 can be increased by creating fusion proteins between the reductase from Bacillus megaterium BM3 (BMR) and the N-terminally modified P450 3A4 (3A4-BMR). In this work, we aim at increasing stability and coupling efficiency by varying the length of the loop connecting the two domains to allow higher inter-domain flexibility, optimizing the interaction between the domains. Starting from the construct 3A4-BMR containing the short linker Pro-Ser-Arg, two constructs were generated by introducing a 3 and 5 glycine hinge (3A4-3GLY-BMR and 3A4-5GLY-BMR). The three fusion proteins show the typical absorbance at 450 nm of the reduced heme-CO adduct as well as the correct incorporation of the FAD and FMN cofactors. Each of the three chimeric proteins were more stable than P450 3A4 alone. Moreover, the 3A4-BMR-3-GLY enzyme showed the highest NADPH oxidation rate in line with the most positive reduction potential. On the other hand, the 3A4-BMR-5-GLY fusion protein showed a Vmax increased by 2-fold as well as a higher coupling efficiency when compared to 3A4-BMR in the hydroxylation of the marker substrate testosterone. This protein also showed the highest rate value of cytochrome c reduction when this external electron acceptor is used to intercept electrons from BMR to P450. The data suggest that the flexibility and the interaction between domains in the chimeric proteins is a key parameter to improve turnover and coupling efficiency. These findings provide important guidelines in engineering catalytically self-sufficient human P450 for applications in biocatalysis.